2021
DOI: 10.20302/nc.2021.30.22
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and plankton communities in mariculture water sources: a case study in Nampu and Sembukan seawaters, Wonogiri, Indonesia

Abstract: Seawaters in Indonesia, part of the tropical marine ecosystem, have great microbial and plankton diversity. Seawater is used as a water source for marine aquacultures, such as shrimp, milkfish, lobster, and mud crab. Sustainability of environmental resources for supporting aquaculture activities can be assessed by analyzing the actual conditions of the water source environment, including bacterial and plankton communities. However, the characteristics of bacteria and plankton communities in Indonesian seawater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…High-throughput sequencing (HTS) based on the bacterial 16S rRNA gene has been widely used as a comprehensive technique to identify the bacterial diversity in aquaculture pond water, sediment, and intestinal tract of farmed shrimp. Southern sea waters such as in Nampu and Sembukan waters, Wonogiri Regency, showed that Actinobacteria and Firmicutes are the dominant bacteria followed by Bacteroidetes and Cyanobacteria groups [9]. The 16S rRNA bacterial analysis of the shrimp rearing water in Banyuwangi proved the dominance of Proteobacteria, Bacteroidetes and Firmicutes, and the shrimp's intestinal tract also had almost similar bacterial diversity [10].…”
Section: Introductionmentioning
confidence: 98%
“…High-throughput sequencing (HTS) based on the bacterial 16S rRNA gene has been widely used as a comprehensive technique to identify the bacterial diversity in aquaculture pond water, sediment, and intestinal tract of farmed shrimp. Southern sea waters such as in Nampu and Sembukan waters, Wonogiri Regency, showed that Actinobacteria and Firmicutes are the dominant bacteria followed by Bacteroidetes and Cyanobacteria groups [9]. The 16S rRNA bacterial analysis of the shrimp rearing water in Banyuwangi proved the dominance of Proteobacteria, Bacteroidetes and Firmicutes, and the shrimp's intestinal tract also had almost similar bacterial diversity [10].…”
Section: Introductionmentioning
confidence: 98%